ANALISIS RISIKO KEBANGKRUTAN DENGAN METODE ALTMAN Z-SCORE, SPRINGATE, DAN ZMIJEWSKI PADA PERUSAHAAN HIBURAN KOREA YANG TERCATAT DI BURSA KOREA TAHUN 2012 – 2016 - A.Kadim A.Kadim; Adji Suratman; Muhammad Abdul Muis (Prodi Manajemen Universitas Pamulang, 2019)
ABSTRACTThis study aims to analyze the risk of bankruptcy in Korean entertainment companies listed on the Korean Exchange in 20122016. The research methodology used is a comparative descriptive method with panel data and quantitative data obtained on the Korean Exchange. Sampling technique using purposive sampling method with data during the period of 2012 until 2016. Data analysis techniques used are different test techniques. The results of this research showed that calculation with altman zscore was able to predicts 19 non-bankrupt companies, 3 companies in grey area, and 3 bankrupt companies. Whereas the calculation of Springate method was able to predicts 16 nonbankrupt companies and 9 bankrupt companies. And the calculation of Zmijewski method was able to predicts 25 non- bankrupt companies and 0 bankrupt companies. Compared with all these three method. The Springate method is the most effective method in predicting bankruptcy of risk companies. The Springate is more effective than the Altman Z-Score and Zmijewski methodKeyword : Bankruptcy Analysis, Altman Z-Score, Springate, Zmijewski, Korean Entertainment